2022
DOI: 10.33137/jrmh.v5i2.37890
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Co-production, Lived Experience and the Shared Learning Environment within the Development and Early Delivery of a Recovery College.

Abstract: Objective: This study sought to explore and value the experiences of the service users, staff, carers and volunteers who were involved in the development and early establishment of a recovery college in a large mental health Trust in the United Kingdom. Research Design and Methods: This qualitative study used Interpretative Phenomenological Analysis (IPA) to explore the experiences of 25 participants who were involved in the design, development and early delivery phases of the recovery college. Data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study identified co‐production occurring amongst students and peer trainers whereas other RC evaluations have identified co‐production as the preserve of peer trainers, 15 , 45 particularly during periods of service development and change. Bester et al 24 and Ali et al 46 identify this as primarily due to the challenges of embedding RC activity within a host organization more accustomed to engaging co‐productively with specific ‘experts by experience’ rather than with a cohort of service users. As an independent RC, RiM has never faced this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified co‐production occurring amongst students and peer trainers whereas other RC evaluations have identified co‐production as the preserve of peer trainers, 15 , 45 particularly during periods of service development and change. Bester et al 24 and Ali et al 46 identify this as primarily due to the challenges of embedding RC activity within a host organization more accustomed to engaging co‐productively with specific ‘experts by experience’ rather than with a cohort of service users. As an independent RC, RiM has never faced this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Given that much of society has been developed in a way that serves the majority, to the detriment of individuals with qualities that deviate from what is socially deemed as normative, we must respect that the interests of people with diverse needs are equally important, and work towards creating a world in which these interests are recognized and accommodated. As illustrated in the Ali et al article, valuing, centering, and highlighting the voices of lived experience is essential in pursuit of equity, diversity, inclusion, and anti-discrimination (4) .…”
mentioning
confidence: 99%